Analisis Ideologis Hadis-Hadis dan Literasi Masyarakat Tentang Informasi Wabah Terhadap Pendidikan di Masa Pandemi - Jimi Muhamad; Diaz Gandara Rustam (Nusantara: Jurnal Pendidikan Indonesia, 2021)
The discussion about the outbreak during the current pandemic is quite interesting and has always been the main topic on several online media sites. Among the online media websites talking about the outbreak is Republika.co, Akurat.co and Islam nu.or.id. Information related to the outbreak in news streams on the Republika.co, Akurat.co and Islam nu.or.id websites always brings pros and cons. This is influenced by the level of public literacy of all forms of information circulating in the media. Because as we know that every information must have a specific purpose. Among those who often echo their aspirations in cyberspace are positivists and constructionists. This study aims to understand the positivist and constructionist ideologies contained in the plague tradition spread on the Republika website, Akurat. co, and Islam.nu. or.id and the level of public literacy awareness in consuming all forms of information that have an impact on the learning process and quality of education during the pandemic. This research uses descriptive qualitative research. Based on the analysis of the data, the following conclusions were drawn: First, the ideology that accompanies the hadiths about the plague in the Republika.co publication is Constructionist ideology. Based on the researcher's analysis, he found several constructionist characteristics, which stated that the news was the result of the construction of media interests and in the submission of the article also included authentic and doif hadith as comparisons. Second, the ideology that accompanies the hadiths about the epidemic in the Akurat.co media is a positivist ideology. Based on the researcher's analysis, most of the hadiths about the plague published on Akurat.co are about steadfastness in facing difficult times, all of which are blessings for those who are patient and punishment for those who despair. Third, the ideology that accompanies Islam.nu.or.id is a positivist ideology. Based on the results of the analysis of researchers who found that most of the published hadiths about the plague were about how the attitude of Muslims when exposed to the plague was to be patient and trustworthy.